FRI0640 Structural damage progression in lupus arthritis: a prospective observational study. (15th June 2017) - Tani, C; Sedie, A Delle; D'Aniello, D; Stagnaro, C; Carli, L; Vagelli, R; Balestri, F; Accogli, S; Caramella, D; Mosca, M
Abstract : Background: Joint involvement is one of the main causes of chronic pain and disability in SLE patients (pts); despite arthritis in SLE is usually considered mild, joint erosions and deformities can be observed with significant impact on patient's quality of life. Imaging techniques are more sensitive than joint count in detecting synovitis and early joint damage. Objectives: This study was aimed at evaluating the progression of joint damage in SLE and at evaluating predictive factors for damage accrual Methods: Consecutive SLE pts with active hand-wrists synovitis (detected by joint count and/or ultrasounds) were enrolled in this 5-years prospective observational study. Clinical assessments as well as joint ultrasound (US) and MRI were performed at baseline and after 5 years. Each patient underwent a non-dominant hand–wrist US examination using a Logiq 9 with a linear probe operating at 14 MHz. Synovitis was defined as the presence of synovial hypertrophy and/or the presence of power Doppler signal (PD). A non-dominant hand–wrist MRI study with a 0.3 T extremity dedicated machine to evaluate the presence of bone erosions (BE) and bone marrow edema (BME) was also performed. Coronal and axial T1-weighted gradient-echo images and coronal STIR images were acquired. The images acquired were scored according to the RAMRIS scoring system for RA by a trained radiologist unaware of the clinical picture and diagnosis. Results: Fifty-seven pts were enrolled (female 91.2%, mean age 44±12.2 years, mean disease duration 15.9±9 years);43 (75.4%) completed the follow-up, 3 died (5.2%) and 11 (19.4%) were lost to follow-up. At baseline, 7 (12.3%)satisfied criteria for Jaccoud arthropathy (JA) and 7 (12.3%) had a recent onset arthritis (<1 year of duration). 22 pts (28.6%) showed clinical signs of synovitis, 56 (98.2%) presented positive hand-wrists US (synovitis) and in 14 (24.6%) PD signal was also recorded. Six pts (11.76%) already showed erosions at standard X-Ray, while MRI revealed at least one BE in 30 and 54 patients respectively, for a cumulative mean erosive burden of 9.2 erosions (range 1–63). After 5 years of follow-up, 34 pts consented to repeat the assessment; 11 (33%) had JA and 18 (29%) were still presenting clinical signs of synovitis; 28 pts (82.3%) showed synovitis at US with PD in 7 cases (20.5%). The final mean erosive burden resulted 12.3 (range 2–82) with a significant increase from the baseline evaluation (p=0.001). Overall, 16 pts accrued joint damage. Interestingly, erosion progression was observed also in 12 pts with negative joint count but positive US at baseline. The presence of PD at US and BME at baseline was associated with higher erosive burden at follow-up (p=0.03 and p=0.02 respectively) Conclusions: Arthritis in SLE can be persistent over time and progress to joint damage even in a short tem period despite treatment; normal joint count at physical examination but US findings of synovitis can be associated with erosion progression over time. The presence of PD at US and bone marrow edema at MRI are associated with a more severe damage progression. US and MRI can be a valid help for the clinician to identify patients at higher risk of severe damage to be treated with a more aggressive therapeutic strategy targeting arthritis. Disclosure of Interest: None declared